2005
DOI: 10.1111/j.1440-1746.2005.03903.x
|View full text |Cite
|
Sign up to set email alerts
|

Response to vaccination against hepatitis B in patients with Behcet's disease

Abstract: These preliminary findings might suggest that the majority of patients with Behcet's disease develop protective antibody response after hepatitis B vaccination and that the immune response against hepatitis B surface antigen is adequate, efficient and intact.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…Data on the efficacy of hepatitis B vaccination in AIIRD patients are lacking, but antibody concentrations are considered to correlate well with protection. Hepatitis B vaccination was immunogenic in most patients with AIIRD,153–156 although two open label small studies reported an insufficient humoral response to HBV vaccine in AIIRD patients treated with bDMARDs 157 158. Furthermore, high-dose HBV vaccination did not increase the humoral response rate 158…”
Section: Resultsmentioning
confidence: 99%
“…Data on the efficacy of hepatitis B vaccination in AIIRD patients are lacking, but antibody concentrations are considered to correlate well with protection. Hepatitis B vaccination was immunogenic in most patients with AIIRD,153–156 although two open label small studies reported an insufficient humoral response to HBV vaccine in AIIRD patients treated with bDMARDs 157 158. Furthermore, high-dose HBV vaccination did not increase the humoral response rate 158…”
Section: Resultsmentioning
confidence: 99%
“…However, no comparative studies have been published so it is impossible to distinguish whether the immunosuppressive treatment, the disease activity of the AIIRD or the natural course of chronic hepatitis B infection was the cause of the hepatitis flare. Hepatitis B vaccination is efficacious in most patients with AIIRD 5557. Vaccination for hepatitis A and/or B is only recommended when the risk of contracting these infections is increased (travel to or residence in endemic countries for hepatitis A and/or B); increased risk of exposure or proven exposure to hepatitis A and/or B (eg, because of medical profession, infected family member or contacts), only when protective antibodies against hepatitis A and/or B are absent.…”
Section: Resultsmentioning
confidence: 99%
“…120 In an uncontrolled study of HBV vaccination of 13 patients with Behçet disease, disease activity was not increased, with the exception of the development of oral aphthae in three patients. 121 Human papillomavirus vaccine A French case-control study including 211 patients with incident cases of autoimmune disease and 875 matched healthy individuals did not show an association between HPV vaccination (with Gardasil®, Merck, USA) and development of autoimmune disease. 146 Although anecdotal evidence exists of the incidence and relapse of SLE after HPV vaccination, 147,148 in a study that recruited 50 patients with SLE with low disease activity (median SLEDAI = 4), no increase in disease flares was observed after Gardasil® vaccination in comparison with 50 unvacci nated matched patients with SLE (0.22 versus 0.20 flares per patient per year).…”
Section: Hepatitis B Vaccinementioning
confidence: 99%